A stakeholder communication case study on the right of way acquisitions of the Subic Clark Tarlac Expressway project - Velasco, Dante Martinez (University of the Philippines Diliman, 2011)
"This is a case study on the communication processes utilized by a state corporation, highlighted by a strategic shift that was responsible for the project's turnaround. The study focused on the acquisition of right of way for 93.77-kilometer infrastructure called the "Subic Clark Tarlac Expressway". A right-of-way acquisition (ROWA) program, an integral part of a larger construction project, has been largely recognized to be a more difficult effort than the construction degment itself, because it involves people who would be asked to give up their lands. The SCTEX implemented two approaches in dealing with project-affected persons during the right-of-way acquisition. The first approach failed halfway toward project completion, and so the second approach had to be adopted quickly to save the project. The first approach was strong in engineering and financial negotiation, but weak in human communication. Midway into the project, the Bases Conversion and Development Authority, identified here as the project owner, faced a growing public resistance manifested in incidence of violence - and faced a more alarming problem: the project may not meet its timetable. Accounts of the first approach and the shift to communication-driven approach are the substance of this study. It involved focus group discussion with the seven community relations (ComRel) workers and focus interviews with seven officials and consultants of the Bases Conversion and Development Authority (BCDA). The study also involved focus interviews with 22 project-affected persons (PAPs) in their respective homes - complemented by document analyses to have an account of the ROWA effort. A number of communication theories provided that basis for the theoretical and conceptual framework of the study, which served as the roadmap to the study's qualitative research. Theories on compliance gaining, exchange, convergence and a study of Filipino socio-cultural values were brought to bear on the study, highlighted by the timely adoption of a communication-driven strategy, complemented by a project structure that placed the communication-oriented ComRel workers as the leaders of the team geodetic engineers, financial negotiators, and security personnel. The study has shown the primacy of communication in stakeholder communication, especially as it asked people to give up something of value - like a piece of land. The study had also shown the need for related communication theories to be reviewed as to their applicability. For example, the convergence model was found to be strong in process, but provides no cue on how to handle the content of the process. In this study, the quality and suitability of messages ensured that the process of exchange continued, because both parties did not want to terminate the communication process. Any too hostile content could have aborted the convergence process. The social penetration theory, which could have been useful to explore the developing "intimacy" between ComRel workers and the stakeholders, could not be pursued to its full fruition because it was used for a project that had a predetermined time-bound beginning and ending, which then cut short the relationship. This is the study's contribution to the body of knowledge on applying communication principles to a construction-related activity."